Interplay of LIS1 and MeCP2: Interactions and Implications With the Neurodevelopmental Disorders Lissencephaly and Rett Syndrome - Keidar, Liraz; Gerlitz, Gabi; Kshirsagar, Aditya; Tsoory, Michael; Olender, Tsviya; Wang, Xing; Yang, Ying; Chen, Yu-Sheng; Yang, Yun-Gui; Voineagu, Irina; Reiner, Orly (Frontiers in Cellular Neuroscience, 2019)
LIS1 is the main causative gene for lissencephaly, while MeCP2 is the main causative gene for Rett syndrome, both of which are neurodevelopmental diseases. Here we report nuclear functions for LIS1 and identify previously unrecognized physical and genetic interactions between the products of these two genes in the cell nucleus, that has implications on MeCP2 organization, neuronal gene expression and mouse behavior. Reduced LIS1 levels affect the association of MeCP2 with chromatin. Transcriptome analysis of primary cortical neurons derived from wild type, Lis1+/-, MeCP2-/y, or double mutants mice revealed a large overlap in the differentially expressed (DE) genes between the various mutants. Overall, our findings are important for understanding the molecular mechanisms involved in the neurodevelopmental disorders lissencephaly and Rett syndrome caused by dysfunction of LIS1 and MeCP2, respectively.